THE EFFECT OF SPECIAL EXERCISES IN DEVELOPING SOME ASPECTS OF MUSCULAR STRENGTH AND WHIP SHOOTING IN HANDBALL FOR PLAYERS OF BASRA EDUCATION TEAM (ResearchJet Journal of Analysis and Inventions, 2023)
The effectiveness of Handball is one of the activities that need an accurate studies in order to achieve the digital achievement of this event, as the great development in mathematical achievements and good link between the different sciences has been discussed in the training of beginners and the emerging, and here the importance of the research came to add something new.